A STUDY ON CONTACT DERMATITIS TO HAIR DYE AND HENNA - Neerja Puri; Asha Puri (Our Dermatology Online, 2013)
P- Phenylenediamine is an oxidative chemical that is frequently used as a permanent hair-coloring agent. It is added to henna to increase the intensity and longevity of the tattoo and expedites its drying time. Henna itself is a greenish brown vegetable coloring made from the leaves of Lawsonia inermis and rarely causes allergic contact dermatitis. The addition of PPD causes the contact sensitization to black henna. Serious adverse skin reactions to permanent hair dyes and temporary black tattoos have been reported. As temporary tattoos have become fashionable among adolescents, the risk profile for p-phenylenediamine (PPD) sensitization of the population has changed simultaneously with an increasing use of hair dyes in this age group. With increased popularity of body art such as body piercing and tattooing, an increase in temporary henna tattoos has also occurred. Although the appeal of non-permanence exists for henna tattoos, dermatologists have begun to see numerous cases of allergic contact dermatitis linked with a certain type of henna. We selected 50 patients using hair dye and henna for our study. Patch testing was done in all the patients using Indian standard series of antigens. Regarding to the side effects to hair dye and henna and itching was the commonest symptom seen in 16% patients, erythematous scaly plaques were seen in 10% patients, vesicular reactions were seen in 6% patients, angioneurotic oedema and contact urticaria was seen in 4% patients each and anaphylaxis and keloidal reaction was seen in 2% patients each.